LAND SUBSIDENCE CAUSED BY GROUNDWATER EXPLOITATION IN THE HANGZHOU-JIAXING-HUZHOU PLAIN, CHINA - Li Ch.; Tang X.; Ma T. (My University, 2006)
Hangzhou-Jiaxing-Huzhou Plain in northern Zhejiang Province, located between the Yangtze and Qiantang Rivers, is one of the regions where economic development is most rapid in China. Geological and hydrogeological surveys reveal a multi-layered aquifer system beneath the plain, which includes Holocene phreatic water layers and Pleistocene confined aquifers. Based on the historical records of groundwater extraction, groundwater levels, and ground settlement from 1964 to 2000, it is shown that ground subsidence has resulted from the continuously increasing extraction of groundwater from deep confined aquifers, and that the evolution of land subsidence can be characterized by a multifractal model. Based on this model, a set of empirical power-law relations have been established between: the land subsidence velocity and the annual groundwater extraction; groundwater drawdown and the annual land subsidence velocity; and the amount of land subsidence and the associated area of land. A set of indices are proposed for evaluating dynamic evolution of groundwater exploitation and land subsidence for the Hang-Jia-Hu Plain, from which the critical degree of evolution of land subsidence in the near future can be estimated using data on groundwater exploitation and water level changes.
Keywords: SUBSIDENCE; NUMERICAL MODELING; OVER-ABSTRACTION; FRACTAL ANALYSIS; ZHEJIANG PROVINCE; Holocene; Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен